A new social-family model for eating disorders: A European multicentre project using a case–control design. (1st December 2015) - Krug, Isabel; Fuller-Tyszkiewicz, Matthew; Anderluh, Marija; Bellodi, Laura; Bagnoli, Silvia; Collier, David; Fernandez-Aranda, Fernando; Karwautz, Andreas; Mitchell, Sarah; Nacmias, Benedetta; Ricca, Valdo; Sorbi, Sandro; et al.
Abstract: Objective: To examine a new socio-family risk model of Eating Disorders (EDs) using path-analyses. Method: The sample comprised 1264 (ED patients = 653; Healthy Controls = 611) participants, recruited into a multicentre European project. Socio-family factors assessed included: perceived maternal and parental parenting styles, family, peer and media influences, and body dissatisfaction. Two types of path-analyses were run to assess the socio-family model: 1.) a multinomial logistic path-model including ED sub-types [Anorexia Nervosa-Restrictive (AN-R), AN-Binge-Purging (AN-BP), Bulimia Nervosa (BN) and EDNOS)] as the key polychotomous categorical outcome and 2.) a path-model assessing whether the socio-family model differed across ED sub-types and healthy controls using body dissatisfaction as the outcome variable. Results: The first path-analyses suggested that family and media (but not peers) were directly and indirectly associated (through body dissatisfaction) with all ED sub-types. There was a weak effect of perceived parenting directly on ED sub-types and indirectly through family influences and body dissatisfaction. For the second path-analyses, the socio-family model varied substantially across ED sub-types. Family and media influences were related to body dissatisfaction in the EDNOS and control sample, whereas perceived abusive parenting was related to AN-BP and BN. Discussion: This is the first study providing support for this new socio-family model, which differed across ED sub-types. This suggests that prevention and early intervention might need to be tailored to diagnosis-specific ED profiles. Highlights: Our socio-family model operated uniquely for eating disorder sub-types. Verbally abusive parents were related to eating disorders with bulimic symptoms. Influences from the family and the media had a broad impact in EDNOS and controls. Prevention should be tailored to diagnosis-specific eating disorder profiles.